Combating ‘inflammaging’ through a Mediterranean whole diet approach: the NU-AGE project rationale - Santoro, A.; Pini, E.; Scurti, M.; Palmas, G.; Berendsen, A.; Brzozowska, A.; Pietruszka, B.; Sczenziska, A.; Cano, N.; Meunier, N.; de Groot, C.P.G.M.; Feskens, E.; et al. (Free radical biology & medicine, 2013)
The development of a chronic, low grade, inflammatory status named "inflammaging" is a major characteristic of aging which plays a critical role in the pathogenesis of age-related diseases. The NU-AGE rationale is that a one year Mediterranean whole diet (considered by UNESCO a heritage of humanity), newly designed to meet the nutritional needs of the elderly, will reduce inflammaging in fully characterized subjects aged 65-79 year of age, and will have systemic beneficial effects on health status (physical and cognitive). Before and after the dietary intervention a comprehensive set of analyses, including omics (transcriptomics, epigenetics, metabolomics, metagenomics) will be performed to identify the underpinning molecular mechanisms. NU-AGE will set up a comprehensive database as a tool for a systems biology approach to inflammaging and nutrition. NU-AGE is highly interdisciplinary, includes leading research centres in Europe on nutrition and aging, and is complemented by EU multinational food industries and SMEs, interested in the production of functional and enriched/advanced traditional food tailored for the elderly market, and European Federations targeting policy makers and major stakeholders, from consumers to EU Food & Drink Industries.